Optical variability, rotation period, and inclination angle of the M9.5 dwarf BRI 0021−0214. Issue 3 (12th November 2022) - Dulaimi, S; Golden, A; Boyle, R P; Butler, R F
ABSTRACT: We report I -band photometric observations of the radio-detected M9.5 dwarf BRI 0021−0214, obtained with the Galway Ultra Fast Imager on the 1.8 m Vatican Advanced Technology Telescope (VATT) at Mt. Graham International Observatory, Arizona. In total, 19 h of observations over a 73 d baseline were obtained. BRI 0021−0214 was shown to exhibit modulated emission with a period of 3.052 ± 0.004 h with a mean amplitude variability of 0.0044 mag. When combined with rotational velocity data obtained from previous work, our newly discovered rotation period gives an inclination angle of 51.7^+5.0_-4.5 deg for the rotation axis of BRI 0021-0214 relative to our line of sight. Previous studies have reported that the most plausible cause for optical variability from this dwarf is a consequence of suspended co-rotating dust clouds in its atmosphere. However, reports of enhanced Hα and intermittent coherent radio emission suggest the possibility of auroral activity in its magnetosphere. Further, more coordinated multiwavlength observations of this dwarf could fully resolve the nature of this elusive rapid-rotator object's observational properties.